Spectrochemical determination of effects on rat liver of binary exposure to benzo[a]pyrene and 2, 2′, 4, 4′‐tetrabromodiphenyl ether. Issue 11 (23rd March 2021) - Liu, Shu‐Zhen; Luo, You‐Hong; Morais, Camilo L. M.; Ma, Xiao‐Jun; Yang, Li‐Jun; Tan, De‐Chan; Li, Jin‐Bo; Liao, Bao‐Yi; Wei, Yuan‐Feng; Martin, Francis L.; Pang, Wei‐Yi
Abstract: Benzo[ a ]pyrene (B[ a ]P) and polybrominated diphenyl ethers (PBDEs) are persistent environmental contaminants. The effects in organisms of exposures to binary mixtures of such contaminants remain obscure. Attenuated total reflection Fourier‐transform infrared (ATR‐FTIR) spectroscopy is a label‐free, non‐destructive analytical technique allowing spectrochemical analysis of macromolecular components, and alterations thereof, within tissue samples. Herein, we employed ATR‐FTIR spectroscopy to identify biomolecular changes in rat liver post‐exposure to B[ a ]P and BDE‐47 (2, 2′, 4, 4′‐tetrabromodiphenyl ether) congener mixtures. Our results demonstrate that significant separation occurs between spectra of tissue samples derived from control versus exposure categories (accuracy = 87%; sensitivity = 95%; specificity = 79%). Additionally, there is significant spectral separation between exposed categories (accuracy = 91%; sensitivity = 98%; specificity = 90%). Segregation between control and all exposure categories were primarily associated with wavenumbers ranging from 1600 to 1700 cm −1 . B[ a ]P and BDE‐47 alone, or in combination, induces liver damage in female rats. However, it is suggested that binary exposure apparently attenuates the toxic effects in rat liver of the individual contaminants. This is supported by morphological observations of liver tissue architecture on hematoxylin and eosin (H&E)‐stained liver sections. Such observations highlight the difficulties in predicting the endpoint effects in target tissues of exposures to mixtures of environmental contaminants. Abstract : B[ a ]P or BDE‐47 alone or in combination can cause damage to the liver of female rats. We suggest that BDE‐47 and B[ a ]P have similar mechanisms of action in inducing liver damage in rats. It is speculated that binary exposure to these agents can result in attenuated toxic effects in rat liver compared with the effects induced following exposure to individual contaminants.